1988
DOI: 10.1073/pnas.85.15.5531
|View full text |Cite
|
Sign up to set email alerts
|

Photic modulation of a highly sensitive, near-infrared light-scattering signal recorded from intact retinal photoreceptors.

Abstract: On stimulation by green flashes, the isolated, aspartate-treated bovine retina exhibits transient changes in the scattering of near-infrared (880 nm) light. A single com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 24 publications
6
72
0
Order By: Relevance
“…2), where ΔI is the dynamic optical change, and I is the background light intensity. The small magnitude of the transient optical response agreed with previous photodiode measurements of IOSs in the retina 36,37 and other neural tissue. 38,[40][41][42]48 Data showed that both a waves (negative peak) and b waves (positive peak) could be clearly recorded in simultaneous electrophysiological measurements, but a positive-going NIR-transmitted light change dominated the corresponding IOSs (Fig.…”
Section: Fast Photodiode Recordings Of Iosssupporting
confidence: 86%
See 1 more Smart Citation
“…2), where ΔI is the dynamic optical change, and I is the background light intensity. The small magnitude of the transient optical response agreed with previous photodiode measurements of IOSs in the retina 36,37 and other neural tissue. 38,[40][41][42]48 Data showed that both a waves (negative peak) and b waves (positive peak) could be clearly recorded in simultaneous electrophysiological measurements, but a positive-going NIR-transmitted light change dominated the corresponding IOSs (Fig.…”
Section: Fast Photodiode Recordings Of Iosssupporting
confidence: 86%
“…35,36 Recent development of adaptive optics imagers 31,32 allows IOS imaging of phototransduction changes of individual photoreceptors in vivo. Fast IOSs correlated with retinal ON and OFF responses have been detected in eyecup slices.…”
Section: Introductionmentioning
confidence: 99%
“…The Ringer's medium contained 110.0 mM NaCl, 2.5 mM KCl, 1.6 mM MgCl 2 , 1.0 mM CaCl 2 , 22.0 mM NaHCO 3 , and 10.0 mM D-glucose, pH 7.3~7.4. The low-sodium medium was prepared by replacing the NaCl in the Ringer's medium with 110.0 mM choline chloride [7]. All procedures for preparation and study of the retina were performed in a dark room with dim red light illumination.…”
Section: Retinal Preparationmentioning
confidence: 99%
“…Previous studies of isolated ROS [5,6] and of isolated intact retina [7,8] have shown that in response to a visible flash, photoreceptors exhibit an intrinsic near infrared scattering signal. As the ROS movement represents a morphological change in the retina, it is logical to hypothesize that the phototropic response of ROSs is a key component of the light-scattering signal [9], i.e., TRP may also originate from the ROSs.…”
Section: Introductionmentioning
confidence: 99%
“…Photoreceptors (PRs) were determined to be the main source of this effect, and in the following years, this method was used for investigation and quantitative evaluation of the activation of the PR G protein transducin and the time course of transduction events (8)(9)(10) and reviewed in ref. 11).…”
mentioning
confidence: 99%